ПІДВИЩЕННЯ ЕФЕКТИВНОСТІ РОБОТИ МІСЬКОГО ЕЛЕКТРОТРАНСПОРТУ У МІСТІ ДНІПРО З ВИКОРИСТАННЯМ ТРОЛЕЙБУСІВ З АВТОНОМНИМ ХОДОМ - FirsovО. D.; Razghonov, S. A.; Zhir, S. I.; Chenakal, A. I. (Systems and Technologies, 2023)
The article emphasizes the development of a transport and logistics scheme for the transportation of passengers in Dnipro city by trolleybus routes using autonomous trolleybuses. The paper analyzes autonomous trolleybuses, evaluates their properties, features of use, and compares them with other types of trolleybuses. It also compares existing trolleybus routes with possible routes using autonomous trolleybuses. The technical-operational and technical-economic indicators of the transport are calculated, and the expenses for the organization of passenger transportation are determined. As a result of the implementation, the revenue from the transportation of passengers by trolleybuses with autonomous operation along the routes of the city of Dnipro is calculated